The formation of lived faith in children: a partnership between congregation and home - Schoeman, Sarel Jacobus (University of the Free State, 2017)
Youth ministry within the congregation is at peril. The old paradigm is not producing the spiritual leaders and followers of Christ that we hoped for. Even the congregations that invest much of their resources, efforts, labours and time in their youth ministry invest in areas where it is least effective. This deplorable situation appears to be rife, although the research reveals to us a way to address this neglect. The focus of this research is to show where the current youth ministry model falls short, and why it should be changed. We take an in-depth look at the most recent research concerning families and ministry focused on the home. The state of scholarship also encompasses the development of lived faith and best practices to achieve this. From this solid, theoretical framework, this study will proceed to do qualitative analysis research via Focused Group Interviews in three diverse congregations to discern what the current philosophy for faith formation is, and how the parents perceive this. This study will then proceed by applying grounded theory to develop knowledge of the problem, and to formulate a theory that may answer the pragmatic question as to how congregations and parents can be more effective in forming lived faith in their young. This practice-oriented theological project hopes to highlight the partnership between the congregation and the home. Similar to dance partners on a dance floor, the aim of both dancers is to bring to the fore the best in each other. Partners inspire each other to render both of them fluent in the language of faith formation. We believe that this will inspire the next generation to join the dance because of the model presented to them. Lastly, we hope to deduce the transferable concepts that can be applied in congregations everywhere.

Jeugbediening in gemeentes beleef tans ‘n krisis. Die paradigma wat tot op hede gegeld het, het nie die geestelike leiers of navolgers van Christus geskep wat ons gehoop het dit sou nie. Selfs die gemeentes wat baie hulpbronne, moeite en energie spandeer aan hul jeugbediening, sien steeds die wegval van jongmense na geloofsbelydenis. Hierdie hartseer situasie kom wydverspreid voor, al is daar duidelike navorsing wat ons kan help om hierdie probleem aan te spreek. Die fokus van hierdie navorsing is om te wys waar die huidige jeugbedieningmodel tekort skiet en hoekom dit sal moet verander. Ons gaan in diepte kyk na wat die literatuur te sê het in verband met gesinne, en bediening aan huishoudings. Hierdie studie sal ook insluit hoe deurleefde geloof gevorm word en hoe geloofsgewoontes hiertoe aanleiding kan gee. Nadat die teoretiese onderbou gevestig is, sal ons voortbou hierop deur middel van ‘n kwalitatiewe ondersoek met fokus-groep onderhoude in drie uiteenlopende gemeentes, om vas te stel wat die huidige filosofie en praktyk van geloofsvorming behels en hoe ouers dit beleef. Hierdie studie sal dan ‘Grounded theory’ as uitgangspunt gebruik om kennis te versamel van die probleem, en ook ‘n teorie te formuleer wat die pragmatiese vraag kan antwoord, nl. hoe gemeentes en ouers meer effektief kan wees in die vorming van hul kinders se geloof. Hierdie praktyk-gerigte teologiese ondersoek hoop om die klem te laat val op die vennootskap wat tussen die gemeente en die huisgesin bestaan. Soos twee dansers graag die beste in mekaar na vore wil bring, moet hierdie vennootskap die sterkpunte van beide vennote uitlig. Sodoende sal hul vloeiend en vaardig word in die vorming van deurleefde geloof, en mag dit ‘n opkomende generasie inspireer om deel te neem aan hierdie geloofs-dans. Laastens hoop ons om oordraagbare konsepte af te lei wat aangebied en toegepas kan word in alle gemeentes waar deurleefde geloof in kinders ‘n prioriteit is. Sarel Jacobus Schoeman
Thesis (Ph.D. (Practical Theology))--University of the Free State, 2017
Keywords: Youth ministry; Church work with youth; Families -- Religious life; Faith; Christian education